2005
DOI: 10.1002/adic.200590079
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical determination of 6‐Mercaptopurine at silver microdisk electrodes

Abstract: The electrochemical behaviour of 6-mercaptopurine (6-MP) at a microdisk electrode is investigated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The results indicate that 6-MP can be strongly adsorbed on the surface of the static mercury drop electrode (SMDE) and reacts with Ag+ ions which are produced at positive potentials. 6-MP yields a well-defined cathodic stripping signal during the negative scan at about -0.812 V (vs. SCE) in pH 9.0 phosphate buffer solution. The electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, the drug has the potential to be cancer‐causing in humans. Various methods including high performance liquid chromatography (HPLC),2–6 capillary electrophoresis,7–10 electrochemical methods,11, 12 fluorescence,13, 14 and spectrophotometric methods15 have been used for the detection of 6‐MP in plasma. Recently, in order to obtain an effective separation and sensitive detection, some coupled methods such as capillary electrophoresis with laser‐induced fluorescence,16 liquid chromatography with electrochemical detection, 17 and liquid chromatography with microdialysis 18 have been used for monitoring 6‐MP.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the drug has the potential to be cancer‐causing in humans. Various methods including high performance liquid chromatography (HPLC),2–6 capillary electrophoresis,7–10 electrochemical methods,11, 12 fluorescence,13, 14 and spectrophotometric methods15 have been used for the detection of 6‐MP in plasma. Recently, in order to obtain an effective separation and sensitive detection, some coupled methods such as capillary electrophoresis with laser‐induced fluorescence,16 liquid chromatography with electrochemical detection, 17 and liquid chromatography with microdialysis 18 have been used for monitoring 6‐MP.…”
Section: Introductionmentioning
confidence: 99%
“…Studies substantiate that concentrations of 6MP were found to be unexpectedly low and highly variable with marked individual differences. Hence, it was crucial to monitor 6MP plasma concentrations over time, so that individualized dosage regimens could be administered ensuring the adequate drug exposure required to prolong remission [3]. On the other hand, research reports that 6MP is a cytotoxic drug with potential serious side effects of bone marrow toxicity and hepatotoxicity, thus limiting its application [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some electrochemical methods, e.g., polarography [16], voltammetric determination at silver microdisk electrodes [17], amperometric detection at a functionalized multi-walled carbon nanotube (MWCNT)-modified electrode in liquid chromatography coupled with microdialysis [18], voltammetric determination using a graphite electrode modified with [Co (phen) 3 ] 3 + /MWCNT [19], determination of 6-mercaptopurine using modified multiwall carbon nanotubes TiO 2 as a voltammetric sensor [20], and cathodic stripping voltammetric determination at a silver electrode [21], have been reported for the determination of MP. Recently, CEelectrochemical detection (EC) determination in a polymethylmetacrylate biochip with on-chip gold nanoelectrode ensemble working and decouple electrodes was reported for MP [22].…”
Section: Introductionmentioning
confidence: 99%